Magnetic properties dependence in the thick of FePt thin films - Sallica, E. (2009)
In this paper we present a systematic study of the thickness dependence of the magnetic properties of disordered FCC-FePt thin films. Films with thicknesses between 9 nm and 94 nm were prepared by DC magnetron sputtering technique and deposited on naturally oxidized Si (100) substrates at room temperature. X ray diffraction measurements show that the films grow with a texture along the [111] direction, perpendicular to the film plane, and that they are under in-plane planar compressive stress. In-plane magnetic hysteresis loops show that there is a critical thickness of approximately 30 nm above which a significant change of the magnetic domain structure is observed. Thinner films (9 nm ≤ t ≤ 28 nm) show an in-plane uniaxial anisotropy characterized by a square hysteresis loop, while thicker films (35 nm ≤ t ≤ 94 nm) show a magnetization reversal in a two steps process, which is typical for systems that have a stripe-like magnetic domain structure. From the out-of-plane magnetic hysteresis loops it was possible to estimate a relatively weak perpendicular anisotropy, which is the origin of the change in the domain structure.